Pollen counts of sediment core Hoefle-Mire, Northern Central Alps (Kleinwalser Valley/Kleinwalsertal, Austria) - Clemens von Scheffer; Annika Lange; Francois De Vleeschouwer; Joachim Schrautzer; Ingmar Unkel (PANGAEA, 2020)
The presented data consists of low resolution pollen data for a mire (Hoefle Mire) of the Kleinwalser Valley (Kleinwalsertal), Austria, in the the calcareous Northern Central Alps. The records cover approximately 6200 years and were analysed to reconstruct past mire development, landscape change, human land use, disturbance and pollution and to detect prehistoric metallurgy.